2020
DOI: 10.1101/2020.05.13.094516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topologically associating domains and their role in the evolution of genome structure and function inDrosophila

Abstract: Topologically associating domains (TADs) are regarded as functional and structural units of higher-order spatial genome organization of many eukaryotic genomes. However, our knowledge of how evolution affects TADs remains limited. To decipher the evolutionary significance of TADs, we de novo assembled the genome of D. pseudoobscura and created a high-resolution (~800 bp) Hi-C contact map to annotate TADs. Remarkably, more than 40% of TADs between D. pseudoobscura and D. melanogaster are conserved, despite exte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 111 publications
(280 reference statements)
6
31
0
Order By: Relevance
“…2018 ) assemblies. Genome assembly-based SV discovery was also performed using the pipeline previously described ( Liao et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…2018 ) assemblies. Genome assembly-based SV discovery was also performed using the pipeline previously described ( Liao et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in Diptera have demonstrated that syntenic breakpoints tend to occur at the boundaries between TADs (Renschler et al 2019, Liao et al 2020, Lukyanchikova et al 2020. Despite having many breakpoints, with relatively few chromosome translocations, the dipteran chromosomes largely remain intact (Bracewell et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results of gene order conservation are consistent with research of Drosophila topological associated domains (TADs) that showed synteny break points at approximately every 6th gene between D. melanogaster, D. virilis and D. busckii , which have a similar level of divergence as the Drosophila taxa we examined, about 40 Ma of divergence (Renschler et al 2019). In addition, the chromosomal rearrangement across Drosophila tends to occur at TAD boundaries, not inside the loops (Renschler et al 2019, Liao et al 2020). In Anopheles mosquitos, the TAD structures seem to be associated with cytological structures as well (Lukyanchikova et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some controversy on whether genome conformation or transcription is more important to gene control ( Ing-Simmons et al, 2020 ), it is well-established that TAD structure plays a role in transcriptional regulation ( Beagan and Phillips-Cremins, 2020 ). Several studies in Drosophila and other eukaryotes have shown that disruption of TAD boundaries and TAD rearrangements alter enhancer-promoter interactions and dysregulate gene expression ( Liao et al, 2020 ). This has led to suggestions that TAD structure should be highly evolutionary constrained between related species, for example, across dipterans.…”
Section: D Genome Organizationmentioning
confidence: 99%
“…This has led to suggestions that TAD structure should be highly evolutionary constrained between related species, for example, across dipterans. Indeed, TADs have been shown to be conserved across Drosophila species ( Renschler et al, 2019 ; Liao et al, 2020 ; Torosin et al, 2020 ). However, the differences in TAD length reported above between Anopheles spp., Ae.…”
Section: D Genome Organizationmentioning
confidence: 99%